Монтаж микросборок с подложкой из кремния - Spirin, V. G. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
A technology is presented for mounting bare dies with volumetric leads and components in mini-packages onto a silicon board. Several design and technological options for mounting a silicon microassembly onto a metal base are considered.